2018
DOI: 10.1124/dmd.113.053397fullarticlecorrection
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Challenge of Predicting Hepatic Clearance of Compounds Slowly Metabolized by Cytochrome P450 Using a Novel Hepatocyte Model, HepatoPac

Abstract: Generating accurate in vitro intrinsic clearance data is an important aspect of predicting in vivo human clearance. Primary hepatocytes in suspension are routinely used to predict in vivo clearance; however, incubation times have typically been limited to 4-6 hours, which is not long enough to accurately evaluate the metabolic stability of slowly metabolized compounds. HepatoPac is a micropatterened hepatocytefibroblast coculture system that can be used for continuous incubations of up to 7 days. This study ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In suspended hepatocyte assays, low‐CL int compounds frequently display no significant turnover within the incubation period in which enzymatic activity can be maintained. Therefore, an in vitro metabolic stability assay to detect slow turnover for a longer period, such as the Hepatopac, 13 HμREL, 2 and relay methods, 14 have been developed, whereas in vivo prediction methods specific for low‐CL int compounds have not been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In suspended hepatocyte assays, low‐CL int compounds frequently display no significant turnover within the incubation period in which enzymatic activity can be maintained. Therefore, an in vitro metabolic stability assay to detect slow turnover for a longer period, such as the Hepatopac, 13 HμREL, 2 and relay methods, 14 have been developed, whereas in vivo prediction methods specific for low‐CL int compounds have not been developed.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 commercially available compounds were selected, including those expected to have low CL int based on clinical data (<5 ml/min/kg 13 ) and those metabolized by cytochrome P450 (CYP) and non‐CYP enzymes. Because most of these compounds were metabolized in the liver, this study assumed that total CL (CL t ) is equal to hepatic CL.…”
Section: Methodsmentioning
confidence: 99%
“… 54 For instance, Boehringer Ingelheim showed that long-term incubations on MPCCs could be used to predict the clearance of ten low clearance compounds within an acceptable threshold of threefold of reported clinical values, and that compound turnover was twofold higher in MPCCs than in suspension PHHs. 38 In a follow-up study, we showed that MPCCs predicted the clearance of 92% of 26 drugs within threefold of their clinical clearance values [ Fig. 2(d) ], whereas conventional 2D PHH monocultures and PHH suspensions were only 20% predictive and could not metabolize several drugs.…”
Section: Engineered Human Liver Models Validated For Drug Testingmentioning
confidence: 90%
“…Furthermore, 3T3-J2 fibroblasts have advantages for use as a PHH-supporting stromal cell since the fibroblasts are expandable, contact-inhibited, and lack liver- and human-specific functions and gene expression, such as CYP enzymes. 7 The MPCC platform and its variants have been rigorously validated for several applications within drug development, such as prediction of drug clearance, 38,39 drug metabolite identification across different species, 40,41 drug–drug interactions (DDIs), 39,42 DILI prediction, 6,43,44 infection with hepatitis B/C viruses (HBV/HCV), 45,46 malaria infection, 47 and early stages of nonalcoholic fatty liver disease (NAFLD). 36,48,49 We provide representative examples below from pharmaceutical practice where available.…”
Section: Engineered Human Liver Models Validated For Drug Testingmentioning
confidence: 99%
“…Therefore, coculture models, such as Hµrel ® and HepatoPac ® , including primary human hepatocytes cocultured with supporting cell types to allow longer-term incubations with consistent metabolic activity and hepatocyte viability throughout incubation, have been established. Evaluation of these coculture models have focused initially on compounds metabolized primarily via CYP enzymes [45,52,53], but promising quantitative prediction performance has also been demonstrated with compounds metabolized primarily by UGTs [16].…”
Section: In Vitro Methods To Measure Ugt-mediated Drug Metabolismmentioning
confidence: 99%